Attitude of Rural and Urban Undergraduate Students of Aligarh Muslim University towards Computer - Varshney, Anant Kumar (EDUCARE, 2015)
ABSTRACT: Technology is the main support for the students learning developments nowadays. With shifting from the teacher-centred instruction to child-centred instruction, the role, activities, attitudes, reflections of the students become more important concern to overlook the effectiveness of technology in instruction. Computers are the main technology support as a tool for effective learning and teaching process. Computer based instruction and computers programs, tools as itself, provides much facilities and supports to studentsâ educational life. Computers are update mechanism for the education and it is not only for education, these developments affect all global, cultural and economical life standards as well. The computer as productivity tool has great role in education. So, computers have become a necessary part of our life. We are using computers in every aspect of our life. But, there are many villages in India which are very much far from computers. How this absence of computer technology affects attitude of students of rural background? This study strives to find answer of this question. A sample consisting of 50 male and 50 female undergraduate students of AMU (Aligarh Muslim University) was selected. Their attitude was assessed through computer attitude scale constructed by T. Khatoon & M. Sharma (2011). After analysis of data, it was found that rural and urban students, both rural and urban undergraduate students, have favourable attitude towards computer, but rural girls showed less favourable attitude than urban girls.KEY WORDS: Computer, students learning, attitude towards computer, undergraduate students, rural and urban students, gender, and favourable and less favourable attitudes.About the Author: Anant Kumar Varshney is a Research Scholar at the Department of Education AMU (Aligarh Muslim University) in Aligarh, Uttar Pradesh, India. For academic interests, the author can be contacted via e-mail at: anant.0148@gmail.comHow to cite this article? Varshney, Anant Kumar. (2015). âAttitude of Rural and Urban Undergraduate Students of Aligarh Muslim University towards Computerâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.97-104. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (May 13, 2015); Revised (June 29, 2015); and Published (August 25, 2015).